HUBUNGAN PENYAKIT JANTUNG BAWAAN DENGAN STATUS GIZI PADA ANAK DI RSUP PROF. DR. R. D. KANDOU MANADO TAHUN 2009-2013 - Maramis, Pingkan Putri; Kaunang, Erling David; Rompis, Johnny (Universitas Sam Ratulangi, 2014)
Abstract: Congenital heart disease (CHD) is a congenital disorder that is common, with the incidence of 30% of all congenital abnormalities. The incidence of congenital heart disease in developed countries and developing countries ranges from 6-10 cases per 1000 live births, with an average of 8 per 1,000 live births. Nutritional status of a person is basically the person's state of health as a reflection of food consumption and use by the body. Many factors influence the nutritional status of infants and children with congenital heart disease. Nutritional status of patients with CHD is influenced nutrient inputs, energy requirements, dietary components. Objective: Knowing the relationship between congenital heart disease with nutritional status in children. Methods: This study is a retrospective analytic approach. The subjects were all children with congenital heart disease who are hospitalized in the Section of Child Health, Prof. Dr. R. D. Kandou Manado in 2009-2013. The data taken in the form of data gender of the child, the child's age, weight and height as well as nutritional status. Data analysis was performed by Chi-Square test. Result: The number of respondents were 53 children, 34 boys and 19 girls. Types of congenital heart disease is the most common type of Atrial Septal Defect. Most people with experience malnutrition (54.7%), followed by poor nutrition (37.8%) and good nutrition (7.5%). With Chi-Square test of the hypothesis, obtained p-value = 0.045 which suggests a link between congenital heart disease with nutritional status in children. Conclusion: Based on the results of congenital heart disease associated with poor nutritional status in children or less. Keyword: congenital heart disease, nutritional status. Abstrak: Penyakit jantung bawaan (PJB) merupakan kelainan bawaan yang sering dijumpai, dengan angka kejadian 30% dari seluruh kelainan bawaan.1 Insiden PJB dinegara maju maupun negara berkembang berkisar 6 – 10 kasus per 1000 kelahiran hidup, dengan rata-rata 8 per 1000 kelahiran hidup. Status gizi seseorang pada dasarnya merupakan keadaan kesehatan orang tersebut sebagai refleksi dari konsumsi pangan serta penggunaannya oleh tubuh.1 Banyak faktor ikut mempengaruhi status gizi pada bayi dan anak dengan PJB.2 Status gizi penderita PJB dipengaruhi masukan nutrien, kebutuhan energi, komponen diet.1 Tujuan: Mengetahui adanya hubungan antara penyakit jantung bawaan dengan status gizi pada anak. Metode: Penelitian ini bersifat analitik dengan pendekatan retrospektif. Subjek penelitian adalah semua anak dengan penyakit jantung bawaan yang dirawat inap di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado tahun 2009-2013. Data yang diambil berupa data jenis kelamin anak, umur anak, berat badan dan tinggi badan anak serta status gizi. Analisis data dilakukan dengan uji Chi-Square. Hasil: Jumlah responden sebanyak 53 anak, 34 anak laki-laki dan 19 anak perempuan. Jenis PJB yang paling banyak diderita adalah jenis Atrial Septal Defect. Kebanyakan penderita mengalami gizi kurang (54.7%), diikuti dengan gizi buruk (37.8%) dan gizi baik (7.5%). Dengan uji hipotesis Chi-Square, didapatkan p-value = 0.045 yang menunjukkan adanya hubungan antara penyakit jantung bawaan dengan status gizi pada anak. Simpulan: Berdasarkan hasil penelitian didapatkan penyakit jantung bawaan berhubungan dengan status gizi buruk atau kurang pada anak. Kata Kunci: penyakit jantung bawaan, status gizi.